Fear of progression, coping strategies, and associated factors among a sample of Malaysian women with breast cancer - Hui Li Lim; Mohammed K. Suhail; Chun Sen Lim; Aqil M. Daher (Scientific Reports)
Abstract Fear of progression (FoP) is a stressful psychosocial condition that affects health and quality of life. Breast cancer is recognized as the most prevalent cancer among women globally. This study aims to determine the prevalence of FoP, coping strategies, and associated factors among Malaysian female breast cancer survivors. A cross-sectional survey was conducted among 242 female breast cancer patients recruited from the south of Malaysia using simple random sampling method. The questionnaire captured sociodemographic characteristics, clinical factors, coping strategies and FoP level. Factors associated with FoP were investigated using multiple logistic regression analysis. The mean age was 55.1 (± 10.9) years. Majority of them were Malays, attained secondary ducation and above, married, unemployed, and in advanced cancer stages. Most patients had low FoP levels, with a smaller proportion having moderate-to-high FoP levels (10.7%). Higher education (AOR = 5.10, P = 0.050), being employed (AOR = 3.85, P = 0.020), advanced can cer stage (AOR = 4.23, P = 0.030), and adoption of avoidant coping strategy (AOR = 1.19, P = 0.009), were associated with higher FoP level. The level of FoP is low among Malaysian females with breast cancer. Higher levels of FoP were associated with higher educational levels, employment status, advanced cancer stage, and utilization of avoidant coping strategies. The fundamental cognitive process mainly affects FoP, rather than disease-related factors.